Isolation of Gram Positive Bacteria In Sumbawa Wild Honey - Memo Andrianto; Novarina Sulsia Ista'In Ningtyas; Alfiana Laili Dwi Agustin (Universitas Pendidikan Mandalika, 2022)
Sumbawa is one of the areas known as honey-producing areas in Indonesia, one of which is wild honey. Wild honey is a type of honey whose habitat is in the wild. How to find honey in Sumbawa is still fairly traditional. The process of packaging wild honey is also still using the traditional way from taking to packaging which is still traditional, which allows bacterial contamination of honey. The aim of the study was to isolate gram positive in Sumbawa wild honey. This study used 10 honey samples from Sumbawa which were used for isolation of gram-positive bacteria in Sumbawa wild honey and then accommodated in a sample tube. Based on the results of the study, it can be concluded that from 10 samples of Sumbawa wild honey taken from different villages there were gram-positive bacteria.